Insights into the analogy between process optimization and molecular dynamics simulation of the CO2-Monoethanolamine absorption system - Salehi, Ehsan; Rafie, Seyed Faridedin; Fattahi, Tayyebeh; Rafiei, Fatemeh; Kashi, Fatemeh; Abu-Zahra, Nidal; Mahmoudi, Fatemeh (Journal of cleaner production, 2025)
This work focuses on simulating and optimizing CO2 absorption in an industrial absorption column by utilizing Monoethanolamine (MEA) solution. The optimal operating conditions were obtained by the response surface methodology (RSM), via analysis of the effects of the important operational variables (column pressure, initial concentration, and temperature of the amine solution), on the CO2 removal percentage and amine loading capacity. Sobol's approach was applied to assess the sensitivity of the absorption system to the operating variables quantitatively. Results uncovered that the concentration of the amine solution is the most effective parameter influencing CO2 absorption. Returning to the results, CO2 absorption was enhanced by raising the temperature of the amine solution. Moreover, elevating the column pressure resulted in enhancement of CO2 removal due to enhanced solubility of CO2 in the solvent. The highest CO2 removal was obtained at the optimal operating conditions, including solvent temperature of 54 °C, amine concentration of 26 wt%, and column pressure of 6.5 bar. The molecular dynamics simulation technique was also employed to investigate the interaction energy changes of the binary amine-CO2 system at different temperatures and pressures. It was uncovered that the optimal temperature and pressure obtained by MD simulations confirm the results revealed by the process optimization approach. Moreover, MD simulation results disclosed that the absorption mechanism is primarily dominated by electrostatic interactions between the carbon of CO2 and the nitrogen of MEA, with minor contributions of van der Waals forces. In sum, it was disclosed that the simulation results of molecular-scale dynamics can verify and support the macro-scale process optimization outcomes. Process simulation and optimization versus molecular dynamic simulation for monoethanolamine-CO2 absorption system. [Display omitted] •Absorption of CO2 by monoethanolamine in an industrial column was simulated.•Multi-objective optimization of absorption process was assessed using data-based methods.•Sobol analysis indicated column pressure as the most effective variable on absorption.•Molecular dynamic simulation uncovered the influences of pressure and temperature on absorption.•Process simulation results were in agreement with the molecular simulation outcomes.